The Taxpayer's Labor and Reporting Decision: The Effect of Audit Schemes. - Collins, Julie H.; Plumlee, R. David (The Accounting Review, 1991)
The article describes an experiment that examines the effect of three audit schemes on taxpayers' joint or related decisions about the level of labor to be supplied and the amount of income to underreport in the United States. Individuals failed to report between $70 and $79 billion in federal taxes due on legal income received in 1986. This amount is equivalent to approximately 20 percent of federal income taxes due and 40 percent of the federal deficit in that year. This problem can be countered by auditing self-reported income; An audit scheme is the approach by which a taxing authority chooses the self-reports to be audited. The three audit schemes differ principally in the information used by the taxing authority to determine which self-reports of income to audit: no information is used–reports are chosen strictly at random; reported income is the basis for choosing the reports to be audited; an estimate of true income is used in addition to reported income to select audit cases. The taxpayer's labor response to the tax system may not be determined solely by the direct effect of tax rates.